Comparison of right ventricular volume measurement between segmented k-space gradient-echo and steady-state free precession magnetic resonance imaging - Alfakih, Khaled; Thiele, Holger; Plein, Sven; Bainbridge, Gavin J.; Ridgway, John P.; Sivananthan, Mohan U. (Journal of magnetic resonance imaging, 2002)
Purpose To compare right ventricular volume measurements and their reproducibility between steady‐state free precession (SSFP) and conventional turbo gradient‐echo (TGE) imaging. Materials and Methods Right ventricular volumes and observer variabilities were compared between SSFP and TGE in 31 subjects (21 normal volunteers and 10 subjects with heart failure). For further internal validation of the right ventricular volumes, the left ventricle (LV) and right ventricle (RV) stroke volumes were compared for the normal volunteers. Results The volumes as measured by SSFP were significantly larger than for TGE (mean bias end‐diastolic volume [EDV] 11.1 ± 14.2, end‐systolic volume [ESV] 9.8 ± 9.75). SSFP had lower interobserver variability (SSFP EDV −10.1 ± 11.6 vs. TGE EDV −6.2 ± 18.5) and intra‐observer variability (SSFP EDV −2.0 ± 6.3 vs. TGE EDV −6.1 ± 14.8). The mean absolute differences between LV and RV stroke volumes for 21 normal volunteers were: TGE 5.8 ± 12.9 (r2 = 0.72), SSFP 4.6 ± 6.9 (r2 = 0.92). Conclusion SSFP and TGE yield different measurement values of RV volumes with SSFP, providing a more reproducible measurement. J. Magn. Reson. Imaging 2002;16:253–258. © 2002 Wiley‐Liss, Inc.